Airborne LiDAR Point Cloud Data, Drained Lake Basin Study Areas on the North Slope of Alaska, 22-27 July 2021 - Christopher Larsen; Benjamin Jones (Arctic Data Center, 2023)
The 2021 airborne Light Detection and Ranging (LiDAR) data was acquired by the University of Alaska Geophysical Institute for an National Science Foundation (NSF) funded project focused on catastrophic arctic lake drainage in northern Alaska. The data was acquired at six key field study sites that included drained lake basins north of Teshekpuk Lake, perched lakes on the Ikpikpuk River Delta, tapped lakes at Drew Point, the large drained lake basin complex at the Pik Dunes, a lake and drained lake basin complex at the Anaktuvuk River tundra fire site, and the cascading lake drainage events along the Chipp and Alaktak Rivers. This dataset encompasses 300 square kilometers of terrestrial and aquatic tundra settings in northern Alaska. The data were acquired between 22 July and 27 July 2021 at an estimated density of 16-20 points per square meter (ppm) using an Reigl VQ-580ii LiDAR system flying at an altitude of 750 meters above ground level. The vertical accuracy of this dataset is 10 centimeters. The data have been post-processed to WGS84 UTM Zone 5 North in Ellipsoid Heights (meters).